Clinical Features and Outcomes of Paediatric Patients With Isolated Colonic Crohn Disease. Issue 2 (February 2022) - Berger, Tal David; Lee, Huey Miin; Padmanaban, Lavenya Ramasamy; Wine, Eytan; Yerushalmy-Feler, Anat; Hojsak, Iva; Kazeka, Denis; Serban, Daniela Elena; Yogev, Dotan; Ledder, Oren; Lionetti, Paolo; Scarallo, Luca; et al.
ABSTRACT: Objectives: Adult studies suggest that patients with isolated colonic Crohn disease (L2 CD) exhibit unique characteristics differentiating them from patients with ileo-caecal (L1) CD and ulcerative colitis (UC). We aimed to characterize clinical features and outcomes of paediatric patients with L2. Methods: Retrospective data was collected through the Porto Inflammatory Bowel Disease group of the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) on Paediatric patients with L2, L1 or UC at different time-points. Outcome measures included time to first flare, hospital admissions, initiation of anti-tumor necrosis factor-alpha (TNFα) drug, stricture and surgery. Results: Three hundred patients were included: 102 L1, 94 L2 and 104 UC. Rates of hematochezia at presentation were 14.7%, 44.7% and 95.2%, while rates of fever were 12.7%, 26.6% and 2.9%, for patients with L1, L2 and UC, respectively ( P  < 0.001 for all comparisons). Skip lesions were identified in 65% of patients with L2, and granulomas in 36%, similar to L1 patients. Rates of anti-Saccharomyces cerevisiae antibodies (ASCA) and perinuclear antineutrophil cytoplasmic (pANCA) positivity significantly differed between the three groups: 25.4% and 16.7% for patients with L2, compared with 55.2% and 2.3%, and 1.8% and 52.9% for patients with L1 and UC, respectively. Response rates to exclusive enteral nutrition were comparable between L1 and L2 (78.3–82.4%), as was the response to oral steroids (70.4–76.5%) in the three groups. While times to first flare and admission were similar between groups, patients with L1 were commenced on anti-TNFα earlier. Moreover, stricturing phenotype and need for colectomy were very rare in patients with L2. Conclusions: Significant differences are observed in the clinical presentation and outcomes of Paediatric patients with L2, compared to patients with L1 and UC. Abstract : Supplemental Digital Content is available in the text